1979
DOI: 10.1070/qe1979v009n05abeh009038
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the parameters of shell targets for laser thermonuclear fusion using an x-ray schlieren method

Abstract: The axes or cores of extensive air showers have been selected by observing in a cloud chamber cascade showers produced by a single high-energy (>5 x lo9 ev) electron or photon, and an upper limit of 5 m for the spread of such particles has been found. By placing trays of hodoscoped counters at various distances from this core selector it has been possible to determine the relation between density of ionizing particles and distance from the axis for showers of approximately 1 04-105 particles. T h e experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…This approach has also led to the concept of X-DVC, which is based on a global approach to volume correlation (as opposed to standard local approaches where patterns are recognised one by one using the correlation of sub-volumes of the image). The finite element tools also have the advantage 21 Particle tracking (PT) can be used to quantify some fracture mechanics parameters and their evolution during a fast in situ tensile fracture test. 310 a Virtual tomographic slices representing typical crack-tip morphology and its evolution at various steps to failure.…”
Section: Quantitative 3d Fracture Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has also led to the concept of X-DVC, which is based on a global approach to volume correlation (as opposed to standard local approaches where patterns are recognised one by one using the correlation of sub-volumes of the image). The finite element tools also have the advantage 21 Particle tracking (PT) can be used to quantify some fracture mechanics parameters and their evolution during a fast in situ tensile fracture test. 310 a Virtual tomographic slices representing typical crack-tip morphology and its evolution at various steps to failure.…”
Section: Quantitative 3d Fracture Mechanicsmentioning
confidence: 99%
“…Early work focussed on the imaging of pellets used in thermonuclear fusion experiments. 20,21 Grating interferometry 22,23 is a rapidly emerging area for both lab 23,24 and synchrotron sources 25 whereby one or more gratings act as wave-front modulators and/or analyzers. While rather slow because one of the gratings must be scanned, it has the advantage that it can be employed on low brightness sources.…”
mentioning
confidence: 99%
“…Applications of XPCI are extremely vast, ranging from biological and medical to security inspection and materials science. Several approaches exist for obtaining phase-contrast images in the X-ray regime, using large-scale synchrotron facilities and more compact X-ray-tube-based equipment [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The imaging methods, their developments and applications can also be found in recent reviews on the subject [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The method measures the derivative of the phase. The method was first introduced by Goetz et al (1979), Ingal & Beliaevskaya (1995), Davis et al (1995), Chapman et al (1997). Chapman et al (1997) demonstrated that it is possible to determine the phase quantitatively for pure phase objects.…”
Section: Analyzer Based Imagingmentioning
confidence: 99%